Greenhouse Gas Accumulation in the Soil Profile is not Always Related to Surface Emissions in a Prairie Pothole Agricultural Landscape. Issue 3 (10th June 2014) - Gao, Xiaopeng; Rajendran, Nandakumar; Tenuta, Mario; Dunmola, Adedeji; Burton, David L.
Abstract : A field study was conducted to examine the influence of landscape position on greenhouse gases (GHG) accumulation in the soil profile and surface emissions from an undulating cropped field in the Prairie Pothole Region (PPR) of Manitoba. The field was segmented into four landscape elements: cropped Upper, Middle, and Lower, and uncropped Riparian. In fall 2005 and from spring‐thaw through a growing season of flax ( Linum usitatissimum L.) in 2006, soil concentrations of N2 O, CH4, CO2, and O2 at 5‐, 15‐, 35‐, and 65‐cm depths and surface emissions were measured. Gas contents in gaseous and aqueous form were estimated at soil depths of 0 to 65 cm. Spring‐thaw increased concentrations and contents of N2 O at 15 to 35 cm in the Lower and Riparian elements, though surface emissions occurred only in the former. This suggested N2 O accumulated during spring‐thaw in both elements but was consumed under prolonged anaerobic conditions of the Riparian element before reaching the soil surface. For the Lower element, addition of N fertilizer to the soil surface resulted in shallow (5 cm) accumulation of N2 O but higher surface emissions than at spring‐thaw. The Riparian element consistently had the highest CH4 emissions. These occurred after the spring‐thaw N2 O emissions and with the accumulation of CH4 in the soil profile and declining O2 concentration. Soil concentrations and profile contents of CO2, as well as surface emissions, were consistently higher in the Riparian than the cropped elements and showed a similar increase with progression of the growing season. Thus, unlike N2 O and CH4, CO2 was not subject to consumption processes in soil. The results suggest limiting N2 O emissions in depression areas may be possible by shifting N2 O production from the near soil surface to lower depths. Promotion of aeration to encourage CH4 consumption in the soil surface may lower CH4 emissions in wet years. Generally, the accumulation depth of GHG varied across the landscape elements reflecting differences in the biophysical factors controlling production and consumption and, thus, determining the surface emissions.